Lietuvos ir Čekoslovakijos prekybos santykių reguliavimas: derybos ir susitarimai 1931-1939 metais - Bukelevičiūtė, Dalia (Lietuvos istorijos studijos, 2004)
The world great economic depression had influence on Lithuanian economics only in 1931, and then in Czechoslovakia became aware of its negative results earlier. In 1931 the highest possible negative trade balance for Lithuania was a result of great economic depression and the difference between import and export of goods, i.e., 19 mln. Lt. In 1932 in Lithuania was discussed the question of balance decreasing and searching for a new market for Lithuanian agriculture products in Czechoslovakia. At the period of great depression, Czechoslovakia introduced quotas for butter, pigs, eggs, fats, and geese. The quotas were introduced for the products that Lithuania was interested in exporting and to decrease the trade balance with Czechoslovakia. In 1932, Lithuanian representative J. Aukštuolis went to Prague. He had to search for new markets for Lithuanian products and to find contacts with Czechoslovakian trade people and official persons. The official persons of Czechoslovakia didn’t want to give licenses for Lithuanian agricultural products because they wanted to protect their market.  In 1932, in autumn, in Prague after long discussions began negotiations between Lithuanian and Czechoslovakian delegations. The goal of the negotiation was to determine quotas for Lithuania. This negotiation was sharp and serious, but the Lithuanian delegation got quotas for some agricultural products. Since 1932 it was the tradition that the Lithuanian delegation went to Prague and negotiated with Czechoslovakia for quota determination. In 1936 and 1937, quotas were determined by the intermediation of embassies. Czechoslovakia didn’t want to determine quotas for Lithuania because it was afraid of other states' interests. The Lithuanian delegation was satisfied with the negotiation results only in 1932 and in 1934. In 1932-1937, the Czechoslovakian delegation didn’t agree to sign an agreement with Lithuania. All negotiations finished only in oral agreement.  Since 1932 Lithuania began to limit imports, and it influenced Czechoslovakia's interests to export textile products. In 1937, the trade balance was active for Lithuania. Czechoslovakia began to review the trade perspectives with Lithuania because of the change in trade relations. In 1938 and 1939, official persons of Lithuania and Czechoslovakia signed an agreement for trade development. There were determined how much and what products states must sell to each other.